Determination of the macrophyte index MIR as an indicator of water quality in the Pripet river - Nekos, Alla; Boiaryn, Mariia; Tsos, Oksana; Netrobchuk, Iryna; Voloshyn, Volodymyr (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Introduction. The river basin and the catchments of small rivers within it is a complete ecological, hydrological and economic unit with clear boundaries and a set of natural conditions. Increasing the stability of the geosystem of the river basin is impossible without monitoring the dynamics of the state of natural resources and factors of negative impact. A significant part of the water management complex of the Volyn region is the Pripet River basin which has a significant degree of development. The watercourse forms part of the state border between Ukraine and the Republic of Belarus, the tributary basins are located on the territory of both states. The source, lower course and mouth of the Pripet River are on the territory of Ukraine. Therefore, it is necessary to observe the strategic principles of rational nature management to restore and preserve the optimal ecological state of the Pripet River basin. The objective of the work is to assess the ecological state of the Pripet River using bioindication methods and the Macrophyte Index for Rivers (MIR). Methods. Research methods are expeditionary, mathematical statistics, bioindication, and determination of the Macrophyte Index for Rivers (MIR). Results. Four test sites of at least 100 m length each were used to determine the ecological state of the waters of the Pripet River. Research found 48 species of higher aquatic and coastal aquatic plants in the test sites of the Pripet River. All species belong to the division Magnoliophyta, of which 21 species of the class Magnoliopsida (43.75%), and the larger share (27 species, 56.25%) to the class Liliopsida. 35 indicative species of macrophytes were selected in the test sites of the river to determine the Macrophyte Index for Rivers (MIR). According to the MIR classification, the river belongs to lowland watercourses, the macrophyte type M-VIII (organic rivers). MIR calculations established that the river water quality in the test site No. 1 (village of Polozhevo, upper reaches) has a satisfactory ecological state, MIR is 33.84; in the site No. 2 (v. Luchytsi) satisfactory ecological state, MIR is 34.04; in the site No. 3 (v. Liubyaz, border between Volyn and Rivne regions) good ecological state, MIR is 40.6; water quality in the site No. 4 (v. Senchytsi, border with Belarus) has satisfactory ecological state, MIR is 33.57. Conclusions. According to the Macrophyte Index for Rivers, it was established that the Pripet River waters have a satisfactory or good ecological state. This gives reason to state that the research in the test sites and the MIR calculations fully reflect the ecological state of the watercourse, which allows the use of this research algorithm for other rivers of the basin.